2021
DOI: 10.3390/ijerph182010598
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Morbidity in Endometriosis: A Couple’s Study

Abstract: Endometriosis is a chronic gynecological disease that impacts more than 176 million women worldwide, having a strong impact on psychological morbidity. This study aimed to evaluate the contribution of psychological morbidity, in women with endometriosis, taking into consideration the duration of the couple’s relationship and the duration of the disease and also examine whether women’s sexual satisfaction had an impact on their psychological morbidity (actor effect) and on their sexual partners’ psychological m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 52 publications
(90 reference statements)
0
9
0
Order By: Relevance
“…Couples coping with endometriosis report decreased levels of satisfaction and well-being within their lives both individually and as a dyad. 49 This study presented the associations between catastrophizing, a cognitive processing method, and depressive symptoms, sexual satisfaction, partner responses to pain, and pain intensity and unpleasantness for couples coping with endometriosis. Aligning with the Communal Coping Model, our study illustrates the impact of a cognitive load, specifically perceptions of pain and pain catastrophizing, on well-being.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Couples coping with endometriosis report decreased levels of satisfaction and well-being within their lives both individually and as a dyad. 49 This study presented the associations between catastrophizing, a cognitive processing method, and depressive symptoms, sexual satisfaction, partner responses to pain, and pain intensity and unpleasantness for couples coping with endometriosis. Aligning with the Communal Coping Model, our study illustrates the impact of a cognitive load, specifically perceptions of pain and pain catastrophizing, on well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Our study aims were guided by the knowledge that pain catastrophizing is associated with poorer well-being outcomes and quality of life among persons with endometriosis [43][44][45][46][47] and that couples coping with endometriosis have reported challenges with their psychological and relational well-being. 23,24,48,49 Thus, we hypothesized that more pain catastrophizing from both members of the couple would be associated with higher pain intensity and unpleasantness for persons with endometriosis. In addition, we hypothesized that when persons with endometriosis reported more catastrophizing about their pain, they and their partners would report more depressive symptoms, less sexual satisfaction, fewer facilitative partner responses, and more negative partner responses.…”
Section: Aims and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, as endometriosis is a shared experience within the couple [13], several researchers have explored dyadic relations and marital satisfaction in the context of endometriosis [12,14,15]. For example, Facchin and colleagues [14] revealed that women who perceived their partner as being more interested and actively involved in the management of their endometriosis (for instance by accompanying them to medical visits) reported greater relational satisfaction and better dyadic coping.…”
Section: Introductionmentioning
confidence: 99%
“…Endometriosis is associated with symptoms of depression, anxiety [ 14 , 15 ], and heightened feelings of uncertainty [ 16 ], leading to substantial reduction [ 3 ] in health-related quality of life (HRQoL). Dyspareunia, infertility, or decreased general ability to cope with everyday life [ 17 ] might put a strain especially on intimate relationships [ 18 ], impairing relationship satisfaction [ 19 ], and adding to the social burden of endometriosis [ 20 ]. The presentation of physical symptoms seems consistent across populations with different cultural backgrounds and geographical locations [ 7 , 21 ].…”
Section: Introductionmentioning
confidence: 99%